Mid-latitude mesospheric clouds and their environment from SOFIE observations. (November 2016) - Hervig, Mark E.; Gerding, Michael; Stevens, Michael H.; Stockwell, Robert; Bailey, Scott M.; Russell, James M.; Stober, Gunter
Abstract: Observations from the Solar Occultation For Ice Experiment (SOFIE) on the Aeronomy of Ice in the Mesosphere (AIM) satellite are used to examine noctilucent clouds (NLC) and their environment at middle latitudes (~56°N and ~52°S). Because SOFIE is uniquely capable of measuring NLC, water vapor, and temperature simultaneously, the local cloud environment can be specified to examine what controls their formation at mid-latitudes. Compared to higher latitudes, mid-latitude NLCs are less frequent and have lower ice mass density, by roughly a factor of five. Compared to higher latitudes at NLC heights, mid-latitude water vapor is only ~12% lower while temperatures are more than 10 K higher. As a result the reduced NLC mass and frequency at mid-latitudes can be attributed primarily to temperature. Middle and high latitude NLCs contain a similar amount of meteoric smoke, which was not anticipated because smoke abundance increases towards the equator in summer. SOFIE indicates that mid-latitude NLCs may or may not be associated with supersaturation with respect to ice. It is speculated that this situation is due in part to SOFIE uncertainties related to the limb measurement geometry combined with the non-uniform nature of NLCs. SOFIE is compared with concurrent NLC, temperature, and wind observations from Kühlungsborn, Germany (54°N) during the 2015 summer. The results indicate good agreement in temperature and NLC occurrence frequency, backscatter, and height. SOFIE indicates that NLCs were less frequent over Europe during 2015 compared to other longitudes, in contrast to previous years at higher latitudes that showed no clear longitude dependence. Comparisons of SOFIE and the Solar Backscatter Ultraviolet (SBUV) indicate good agreement in average ice water column (IWC), although differences in occurrence frequency were often large. Highlights: Mid-latitude NLCs are five times weaker and less frequent than at high latitudes. Differences in mid vs. high latitude NLCs are due primarily to temperature. Mid-latitude NLC particles have similar radii and meteoric smoke content. NLC were less frequent over Europe in 2015 compared to other longitudes.